2006
DOI: 10.1590/s0074-02762006000600004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rifampin resistance patterns in Mycobacterium tuberculosis strains isolated in Iran by polymerase chain reaction-single-strand conformation polymorphism and direct sequencing methods

Abstract: Mutations in the rpoB locus confer conformational changes leading to defective binding of rifampin (RIF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Eight studies performed the PCR-SSCP assay on culture iso- lates, and two performed it on sputum samples. Eight studies used a standard phenol-chloroform method to extract chromosomal DNA for PCR amplification (3, 12-14, 16, 18, 31, 37), two studies used the cetyltrimethylammonium bromide (CTAB)-NaCl method (11,17) to extract DNA. Seven studies used the same PCR amplification primers (12-14, 16, 17, 18, 31), and three studies used other primers (3,11,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies performed the PCR-SSCP assay on culture iso- lates, and two performed it on sputum samples. Eight studies used a standard phenol-chloroform method to extract chromosomal DNA for PCR amplification (3, 12-14, 16, 18, 31, 37), two studies used the cetyltrimethylammonium bromide (CTAB)-NaCl method (11,17) to extract DNA. Seven studies used the same PCR amplification primers (12-14, 16, 17, 18, 31), and three studies used other primers (3,11,37).…”
Section: Resultsmentioning
confidence: 99%
“…The PCR-SSCP assay is relatively simple and was initially promising. Recently, the PCR-SSCP assay has been used in some studies for the rapid detection of rifampin-resistant M. tuberculosis (3,11,12,17). However, individually, these trials found that the sensitivity and specificity were statistically inconsistent.…”
mentioning
confidence: 99%
“…Specific amino acid substitutions within the regions of the rpoB gene are strongly associated with resistance to other classes of drugs, most notably isoniazid (9,12,18,23,29). Codons 511, 516, 526, and 531 have been reported as the rpoB sites with the most frequent mutations worldwide (1,9,18,20,26,29), although variations in the relative frequencies of the mutations in these codons have been described for M. tuberculosis isolates from different geographic locations (8,18,27,34). These differences reflect the complex and crucial interactions between rifampin and drug targets at the molecular level, where the positions of the affected nucleotide changes seem variable.…”
Section: Discussionmentioning
confidence: 99%
“…Several scanning methods are available for detection of drug resistance mutations, including denaturing gradient gel electrophoresis, conformation-sensitive gel electrophoresis, temperature gradient capillary electrophoresis, denaturing high-performance liquid chromatography (dHPLC), and high-density oligonucleotide arrays (15,20,22,30,31,33). These methods vary in sensitivity and generally either are labor-intensive or require sophisticated instrument to perform analyses.…”
mentioning
confidence: 99%